(6x+9)-2(2x-5)=38

Simple and best practice solution for (6x+9)-2(2x-5)=38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+9)-2(2x-5)=38 equation:


Simplifying
(6x + 9) + -2(2x + -5) = 38

Reorder the terms:
(9 + 6x) + -2(2x + -5) = 38

Remove parenthesis around (9 + 6x)
9 + 6x + -2(2x + -5) = 38

Reorder the terms:
9 + 6x + -2(-5 + 2x) = 38
9 + 6x + (-5 * -2 + 2x * -2) = 38
9 + 6x + (10 + -4x) = 38

Reorder the terms:
9 + 10 + 6x + -4x = 38

Combine like terms: 9 + 10 = 19
19 + 6x + -4x = 38

Combine like terms: 6x + -4x = 2x
19 + 2x = 38

Solving
19 + 2x = 38

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + 2x = 38 + -19

Combine like terms: 19 + -19 = 0
0 + 2x = 38 + -19
2x = 38 + -19

Combine like terms: 38 + -19 = 19
2x = 19

Divide each side by '2'.
x = 9.5

Simplifying
x = 9.5

See similar equations:

| X^3(2x^2+4x)= | | (X+y)(dx-dy)=dy+dx | | 9x+6=6x-12 | | 9-4(5x-3)=1 | | 3cos^2x/3-3=4sinx/3 | | 3.51/4 | | 5/250=d/300 | | x+5.67y=780 | | 6+0=-2y | | kx^3=5x+2 | | lny+4x=x+3lnx | | 5x/10=13x-10 | | 35x+23y=16xy | | 36=2(v+8)-6v | | 24+3=2x+x | | 23+54-x= | | -12x-16x-3=-4(3x-2)-8x | | -2.3n+16=-5n-38 | | log-2b=3 | | 19-x=-2 | | 2/3t=-1/5 | | 5x+13+2=5x+4+7 | | 2.1=7 | | 2cos^2x+1=cosx | | 2x^2+40x+168=0 | | 2+4(3+x)=18 | | C=15n+50 | | 7n+5-2n=20+3n+1 | | 0.60x+1.50+10=13.50 | | 10x+20y+30z=10460 | | 3(-0.4u+1.8)= | | 2/3(x-15)=26 |

Equations solver categories